ANALYSIS CLASSIFICATION OF HOUSEHOLDS WHO RECEIVED "RASKIN" IN SEMARANG CITY USING FUZZY K-NEAREST NEIGHBOR (FKNN) AND SUPPORT VECTOR MACHINE (SVM). (2022) - ISPRIYANTI, DWI; *, *; PRAHUTAMA, ALAN; MUSTAFID, MUSTAFID; SUGITO, SUGITO; WATI, RETNO DIAN IKA
No abstract available